Compressibility of a Cambisol Submitted to Periods of Rotational Grazing and Strategies to Avoid Additional Soil Compaction - Luis Eduardo Akiyoshi Sanches Suzuki; Darcy Bitencourt Junior; Eloy Antonio Pauletto; Ezequiel Cesar Carvalho Miola; Pablo Rostirolla; Gilberto Strieder (Conservation, 2023)
Soil compaction is one of the main causes of soil degradation, and some parameters have been used to characterize it, like those related to compressibility and the degree of compactness. To evaluate the rotational grazing time during winter and the presence and absence of grazing, on the compressibility and degree of compactness of a Cambisol, an experiment was installed and consisted of corn planting for silage, a fallow and pasture planting period, with two treatments evaluating the amount of rotational grazing (two and three times in a period of, respectively, 2 and 3 months), subdivided into the presence and absence of dairy cattle grazing. The mean bulk density value of 1.47 Mg/m3 separates the occurrence (plastic deformation) or not (elastic deformation) of additional soil compaction, while the traffic of machinery and animal trampling should occur with soil moisture lower than 0.23 kg/kg, when the soil has a larger load-bearing capacity. For the conservation of soil structure, our study recommends the permanence of cattle in the plots for 30 to 40 min/day and an exit when the pasture height is 0.07 to 0.10 m, with two or three grazing in a period of, respectively, 2 and 3 months.